Synthesis of Mesoporous Carbons Derived from Hypercrosslinking of Divinylbenzene – 4-Vinylbenzyl Chloride Resin - Wijaya, Ulfia (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2007)
Conducting polymer as the precursor for developing porosity carbon by hypercrosslinked resin networks represent promising material for electrochemical electrodes. 4-Vinylbenzyl Chloride at 90% technical grade and Divinylbenzene at 80% technical grade ware prepared for synthesizing homogeneous gel-type resins via suspension polymerization. Synthesize of hypercrosslinking resin which aimed to produce high porosity carbon was then done by inducing 1,2-Dichloroetane and Iron (III) Chloride. Product of resins was found has the specific surface area 1332 m2.g-1. According to this project, it can be concluded that high surface area of resin in the presence of carbon will yield carbon with high porosity which can increase effective plate area in the development of electrochemical capacitor.